STATUS HARTA YANG DIBUAT DALAM PERJANJIAN PERKAWINAN BERDASARKAN PUTUSAN MK NO. 69/PU-XIII/2015 - Rusmini, Rusmini (Justici, 2024)
ABSTRACK A marriage agreement (huwdjiks or huwelijkse wourwaarden) is an agreement made by two people between a prospective husband and a prospective wife before the marriage takes place. The agreement is a guarantee of certainty so that in the future, if a divorce occurs, no one will be harmed and contains points agreed to by both parties. The approach method used is normative juridical. The purpose of the normative juridical approach is legal research that prioritizes a library approach. Analysis of the data used in this research was carried out descriptively analytically, namely describing the applicable laws and regulations in a comprehensive and systematic manner and then analyzing the problem solving. Every legal decision taken will of course have implications, as does Constitutional Court Decision No. 69/PU-XII/2015. The implications of a marriage agreement made after a marriage are closely related to the status of property and third parties. The status of property that occurs after the marriage takes place becomes separate.